Pengaruh Nilai Belanja Hedonis Dan Gaya Hidup Belanja Serta Gratis Ongkir Terhadap Pembelian Impulsif Pada Pelanggan Shopee Studi Kasus Mahasiswa Universitas Islam Malang - I Bagus Setiyadi; Muhammad Agus Salim; Afi Rahmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of hedonic shopping values, shopping lifestyle, and free shipping on impulse buying. This type of research is Explanatory Research using quantitative methods. The population in this study were students of the Islamic University of Malang. While the sample used in this study was to use Maholtra's opinion so that 80 samples were obtained. The data analysis method used is an instrument test consisting of validity and reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests and heteroscedasticity tests, multiple linear regression analysis, hypothesis testing simultaneous tests, partial tests and coefficient of determination. From the results of the study, it can be seen that simultaneously obtained results that the value of hedonic shopping, shopping lifestyle, and free shipping have a significant effect on impulse buying. Partially obtained results that the value of hedonic shopping has no significant effect on impulse buying, shopping lifestyle effects impulse buying, and free shipping effect on impulse buying. Keywords: Hedonic Shopping Value, Shopping Lifestyle, Free Shipping, Impulse Buying